Creative Artwork of Elementary School Children's Dance Drama Performance Based on Folklore (Folklore) of Kediri City - Sari, Ayu Titis Rukmana; Wahyudi, Wahyudi (Universitas Nusantara PGRI Kediri, 2024)
Problems encountered related to art education include the rareness of alternative literacy of art forms for elementary school students based on culture. Local art products such as the Panji story will be very valuable if elaborated in the world of children in the form of performing arts. Involving children in the creative process of practicing art can provide empirical experience to improve their creativity. This study aims to determine the level of validity, originality of the work and the applicability of drama dance performance art works for elementary school children. The method of developing this drama dance art work is carried out with the stages of observation, exploration, composition and evaluation. The results of the study showed that the product of the creation of elementary school children's drama dance performance art based on folklore is very valid/suitable for use. This is evidenced by the score of 4.80 obtained by the dance expert validator. The validation results are related to the variety of movements, floor patterns, costumes and make-up. While the second validator obtained a score of 5 which means that the Panji Laras drama dance product/work is very valid/suitable for use. The validation results include the level of originality of the work, novelty and applicability for elementary school children. Thus, the work of dance drama performance art entitled Panji Laras is very valid/worthy of being used.